2019
DOI: 10.1002/arch.21599
|View full text |Cite
|
Sign up to set email alerts
|

An omega‐class glutathione S‐transferase in the brown planthopper Nilaparvata lugens exhibits glutathione transferase and dehydroascorbate reductase activities

Abstract: A complementary DNA that encodes an omega-class glutathione S-transferase (GST) of the brown planthopper, Nilaparvata lugens (nlGSTO), was isolated by reverse transcriptase polymerase chain reaction. A recombinant protein (nlGSTO) was obtained via overexpression in the Escherichia coli cells and purified. nlGSTO catalyzes the biotransformation of glutathione with 1-chloro-2,4-dinitrobenzene, a general substrate for GST, as well as with dehydroascorbate to synthesize ascorbate. Mutation experiments revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have found that drug stress can induce or inhibit the expression of GSTs [ 24 ]. For example, the expression of Nilaparvata lugens NLGSTE decreased by 36% after exposure to 0.1 mM aldicarb [ 34 ]; the expression of SLGSTe2 and SLGSTe3 of Spodoptera litura was slightly upregulated after exposure to carbaryl, DDT and deltamethrin, but neither of these could be induced after exposure to malathion [ 35 ]; and the expression of Dugesia japonica GSTs was significantly inhibited after exposure to high concentration of glyphosate for 5 days [ 36 ]. In the present study, the expression of HrGSTm1 in the Malpighian tubules was higher than that in the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that drug stress can induce or inhibit the expression of GSTs [ 24 ]. For example, the expression of Nilaparvata lugens NLGSTE decreased by 36% after exposure to 0.1 mM aldicarb [ 34 ]; the expression of SLGSTe2 and SLGSTe3 of Spodoptera litura was slightly upregulated after exposure to carbaryl, DDT and deltamethrin, but neither of these could be induced after exposure to malathion [ 35 ]; and the expression of Dugesia japonica GSTs was significantly inhibited after exposure to high concentration of glyphosate for 5 days [ 36 ]. In the present study, the expression of HrGSTm1 in the Malpighian tubules was higher than that in the midgut.…”
Section: Discussionmentioning
confidence: 99%